Innovation systems perspectives on developing-country agriculture: A critical review - Spielman, David J. (International Food Policy Research Institute, 2005)
Innovation systems perspectives on agricultural research and technological change are fast becoming a popular approach to the study of how society generates, disseminates, and utilizes knowledge, and how such systems can be strengthened for greater social benefit. The more theoretical innovation systems literature represents a significant change from the conventional, linear perspectives on agricultural research and development (R&D) by providing a framework for the analysis of complex relationships and innovative processes that occur among multiple agents, social and economic institutions, and endogenously determined technological and institutional opportunities. The emerging body of empirical literature is equally significant in that it provides analysis of different forms of cooperation (e.g., research partnerships, knowledge networks, and industry clusters) among state and nonstate actors (e.g., public research organizations, private firms, and producer organizations) in various sectoral, spatial, and temporal contexts. Taken together, the innovation systems framework demonstrates the importance of studying innovation as a process in which knowledge is accumulated and applied by heterogeneous agents through complex interactions that are conditioned by social and economic institutions... This paper begins in Section 2 with a brief overview of the literature on agricultural development and technological change, including a review of the seminal literature on innovation systems and its application to developing-country agriculture. Section 3 sets forth the conventional terminology used in the literature, followed in Section 4 by a model of an innovation system derived from a series of game theoretic and population game models in which heterogeneous agents interact and evolve through strategic patterns of behavior. The strengths and weaknesses of the innovation systems framework—and recommendations for improving the framework—are discussed in Section 5 with respect to developing-country agriculture, followed by concluding remarks in Section 6.